Burning Mouth Syndrome - The Most Common Causes of Our Patients - S. Kaprálová (Česká Stomatologie a Praktické Zubní Lékařství, 2011)
Oral cavity, including lips and labial mucosa in red, constitutes the environment that is daily exposed to many substances that may have an irritative nature and cause many unpleasant sensations. This state is termed as a "dyny", in the foreign literature, a term Burning Mouth Syndrome (BMS) is used in addition to local factors may play a role in the overall effects, possibly combination of both. Stomatodynia divided into stomatodynia in the strict sense, it is not possible to identify any of these factors or stomatodynia in a broader sense, where a comprehensive examination of the precipitating factors can explain. Among the local factors evoking oral cavity irritation, we include allergies to dental materials, galvanic stimulation, changes in microbial flora of the mouth, dry mouth caused by above-mentioned factors and/or reaction to used medication. Thus, the emergence of dyny is governed by the overall health of the patient, the above-mentioned drugs, hormonal and metabolic disorders, neuropathy, angiopathy, radiotherapy and chemotherapy.The aim of our study was to find some of these above-mentioned causes, mainly of a local character, and to relieve the patient's suffering, which can often lead to cancerophobia and often to a substantial reduction of psychological comfort of the patient. In collaboration with the Dermatology Clinic, University Hospital in Olomouc, we searched for possible allergies to dental materials utilizing patch tests, we then monitored other etiopathogenetic factors of stomadynia evaluating detailed examinations.